Obesity Associated Cerebral Gray and White Matter Alterations Are Interrelated in the Female Brain. - Mueller, K.; Horstmann, A.; Moller, H. E.; Anwander, A.; Lepsien, J.; Schroeter, M. L.; Villringer, A.; Pleger, B. (PLoS One, 2014)
Obesity is known to affect the brain's gray matter (GM) and white matter (WM) structure but the interrelationship of such changes remains unclear. Here we used T1-weighted magnetic resonance imaging (MRI) in combination with voxel-based morphometry (VBM) and diffusion-tensor imaging (DTI) with tract-based spatial statistics (TBSS) to assess the relationship between obesity-associated alterations of gray matter density (GMD) and anisotropic water diffusion in WM, respectively. In a small cohort of lean to obese women, we confirmed previous reports of obesity-associated alterations of GMD in brain regions involved in executive control (i.e., dorsolateral prefrontal cortex, DLPFC) and habit learning (i.e., dorsal striatum). Gray matter density alterations of the DLPFC were negatively correlated with radial diffusivity in the entire corpus callosum. Within the genu of the corpus callosum we found a positive correlation with axial diffusivity. In posterior region and inferior areas of the body of the corpus callosum, axial diffusivity correlated negatively with altered GMD in the dorsal striatum. These findings suggest that, in women, obesity-related alterations of GMD in brain regions involved in executive control and habit learning might relate to alterations of associated WM fiber bundles within the corpus callosum.
Keywords: Adult; Cohort Studies; Female; Gray Matter/diagnostic imaging/*pathology; Humans; Magnetic Resonance Imaging; Obesity/diagnostic imaging/*pathology; White Matter/diagnostic imaging/*pathology; Young Adult